Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Cibodas : The Effect of Work Motivation and Work Discipline on the Performance of Employees at the Cibodas Subdistrict Office - Indah Rahma Cahyani; Ratih Hastasari; Wawan Saputra (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This research is driven by the importance of employee performance in achieving organizational goals. Work motivation and work discipline are considered crucial factors influencing performance. The objective of this study is to analyze the simultaneous and partial effects of work motivation and work discipline on the performance of employees at the Cibodas Sub-district Office. The research method employed is quantitative, utilizing primary data obtained through questionnaires. The population of this study comprises all employees of the Cibodas Sub-district Office. Data analysis included validity tests, reliability tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results of the t-test indicate that work motivation (X1) partially has a significant effect on employee performance (Y) with a Sig. value of 0.000 (< 0.05), and work discipline (X2) also has a significant partial effect with a Sig. value of 0.000 (< 0.05). The F-test results show that work motivation and work discipline simultaneously have a significant effect on employee performance with a Sig. value of 0.000 (< 0.05). The partial coefficient of determination for work motivation is 36.3%, and for work discipline is 34.6%. Meanwhile, the multiple coefficient of determination is 71.2%, indicating that work motivation and work discipline explain 71.2% of the variation in employee performance.